Citric acid monohydrate production plant using sugarcane bagasse as substrate in solid-state fermentation a plant design - Arabit, Jimyl M.; Lerin, Maricar T.; Adolacion, Jay R T.; Baynosa, Marjorie L. (Quezon City College of Engineering, University of the Philippines Diliman, 2012)
Citric acid, 2-hydroxypropane-1,2,3-tricarboxylic acid is an acidulant primarily used in the food, pharmaceutical, cosmetics, detergents, and chemical industry and its demand is growing by 5-7 percent due to the improvement in the living standards of the population as the food and beverages market make up about 70 percent of the consumer of citric acid. However, more than 99 percent of its supply in the Philippines is imported, mainly from china. This project proposes as design of the pioneering citric acid plant in the country with an annual production of 10 kilotons to locally compensate the import requirement.Among the agro-industrial wastes in the Philippines, the abundance of sugarcane bagasse is more than then times compared to other such as that of cassava and pineapple. More than 50 percent of the sugarcane bagasse supply in the Philippines comes from the Western Visayas particularly in Negros Occidental and thus there is the recommended plant location. There are three fermentation methods commonly used, namely the surface, submerged liquid and the solid-state fermentation. From the advantages and disadvantages each has to offer, the solid-state fermentation was the chosen process as it is the most cost efficient and thereby minimizing the operating expenses due to lesser amount of water usage, energy usage, and waste production. The microorganism used is a Aspergillus niger LPB BC3. Among the conventional precipitation, liquid extraction method, and the simulated moving bed technology processes for the downstream process, the latter was chosen due to lower operating cost and lesser production of unwanted waste products.The proposed pioneering citric acid plant in the Philippines is found to be economically feasible having a product selling price of P65/kilo which is fairly competitive in the market. It has an annual capacity of producing 10 kilotons of citric acid monohydrate with a return on investment of 18.47 percent, payback period of 5.42 years, net present worth of 239.92 M, and an internal rate of return of 17.81 percent.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Citric acid; Bagasse